Biodiesel Production from Food Industrial Waste of Soybean Oil using a Lipase-nanoparticle Bio-composite Catalyst - Sathish Thanikodi; Saravanan Rathinasamy; Jayant Giri; Aravind Kumar Jagadeesan; Emad Makki (Universitas Muhammadiyah Magelang, 2024)
In this study, a packed-bed reactor was used to produce biodiesel from disposed soybean oil using a lipase-nanoparticle bio composite catalyst. During the transesterification process of the ”˜disposed of/used soybean oil’, different nano catalysts were employed such as nanoparticles of Ni-doped ZnO, Fe3O4, Alkylcelite, Poly-acrylonitrile fibres and Poly-acrylonitrile nanofibrous membrane and they were abbreviated as CI, CII, CIII, CIV and CIV respectively. In each case of biodiesel production, there were two levels of process parameters like flow velocity (such as 0.25 mL/min-1.25 mL/min) and the reaction time (20 and 100 h) were considered for analyses. From the derived biofuel, the biodiesel blends were prepared as B50 (50% diesel and 50% biodiesel) and B75 (25% diesel and 75% biodiesel). The synthesis of biofuel results, in the biodiesel conversion of cepacia lipase with Poly-acrylonitrile nanofibrous membrane nanoparticles being recorded at about 85% at a 1.25 mL/min flow rate, which is the maximum biodiesel conversion among five grades. The shortlisted biodiesel performances were analyzed by varying the engine speed, grade and kind of biodiesel, The observed results were analyzed. The B50CIV and B75CIV blends recorded the maximum BSFC at 1800 rpm engine speed. CO2 emission by diesel is about 2.3 vol% was recorded. It is the highest value compared to biodiesel blends (B50 and B75). The emission of NOx with the B50CII blend was 220 ppm at the engine speed of 1800 rpm. Based on the experimental results, B50CIV serves affordable fuel and is recommended among those tested in this investigation for CI engines.